Phase change energy storage fiber and preparation method of phase change energy storage fiber fabric

By introducing aliphatic alkyl long chains and DOPO phosphorus-containing flame retardant structures into PET fibers and electrospinning with fatty acid eutectic phase change materials, the problem of poor mechanical properties and flame retardant properties of PET fibers is solved. It achieves higher tensile strength, elongation at break and flame retardant properties, and is suitable for a wide range of phase change heat storage applications.

CN119265745AActive Publication Date: 2025-01-07KUNSHAN HUAYANG NEW MATERIAL

Patent Information

Application Number
CN202411691172.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The mechanical properties and flame retardant properties of existing PET phase change fibers are poor, especially the tensile strength and elongation of breaking, and the flame retardant properties are insufficient to meet certain application requirements.

Method used

UV irradiation grafting is performed by adding graft monomer to the polyethylene terephthalate film, introducing aliphatic alkyl long chain and DOPO phosphorus-containing flame retardant structure, and eutectic phase change material with fatty acids Electrospinning is performed to form modified PET fibers, improve the melting temperature and melting enthalpy of the fibers, and enhance the mechanical properties and flame retardant properties of the fibers.

Benefits of technology

It significantly improves the flame retardant properties and mechanical properties of PET fibers, including tensile strength and elongation at break, while enhancing the phase change heat storage properties of the fibers, and is suitable for fiber apparel and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150988190000021
    Figure BDA0005150988190000021
  • Figure BDA0005150988190000031
    Figure BDA0005150988190000031
  • Figure BDA0005150988190000041
    Figure BDA0005150988190000041
Patent Text Reader

Abstract

The invention relates to the technical field of fibers, and discloses a phase-change energy-storage fiber and a preparation method of a fabric of the phase-change energy-storage fiber. A grafting monomer is used for carrying out ultraviolet radiation grafting modification on polyethylene glycol terephthalate (PET), then electrostatic spinning is carried out on the PET and a fatty acid eutectic phase-change material composed of capric acid, lauric acid and the like, and the phase-change energy-storage fiber and the fabric of the phase-change energy-storage fiber are obtained. The obtained phase change energy storage fiber shows different melting temperatures and melting enthalpy values, and has good phase change heat storage performance and flame retardant property. The interface bonding force between the eutectic phase-change material and the PET fiber is improved, and the adverse effect of the eutectic phase-change material on the mechanical property of the PET fiber is reduced, so that the PET fibrofelt keeps relatively high tensile strength, elongation at break and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber technology, and in particular to a preparation method of a phase-change energy storage fiber and a fabric thereof. Background Art

[0002] Phase change materials can absorb and release a large amount of heat during the phase change process, thereby effectively storing thermal energy and regulating temperature. They are a clean and renewable latent heat storage material and are widely used in fiber clothing, construction, battery cooling systems, aerospace, etc. Common phase change materials include paraffin, polyethylene glycol, fatty acids such as stearic acid and their low eutectics.

[0003] Polyester fiber made of polyethylene terephthalate has good breaking strength, elastic modulus, heat resistance and corrosion resistance, and is widely used in fiber clothing, textiles and other aspects. The development of new phase change energy storage polyester fiber fabrics is a research hotspot. Usually, adding phase change materials such as fatty acids will affect the mechanical properties of the fiber such as tensile strength. The Chinese patent with application number 200610037169.X discloses a phase change energy storage ultrafine composite polyester fiber and its preparation method, which uses stearic acid and its ester derivatives as phase change materials and is coated inside the polyester matrix. The obtained polyester fiber has a large specific surface area, high porosity and temperature regulation. However, the polyester fiber of this patent does not show good mechanical strength and flame retardant properties. Summary of the invention

[0004] (I) Technical problems solved: Aiming at the deficiencies of the existing technology, the problems of poor mechanical properties and flame retardancy of PET phase change fibers are solved.

[0005] (II) Technical solution: A method for preparing a phase change energy storage fiber: Step A, add an acetone solution of benzophenone with a mass concentration of 0.3-1 g / L into a reaction container, add a polyethylene terephthalate film after stirring, take out the film, dry and remove the acetone, then add the film to an ethanol solution of a grafting monomer with a mass concentration of 30-150 g / L, irradiate under ultraviolet light in a nitrogen atmosphere, and perform a grafting reaction for 30-90 minutes, take out the film, add it to toluene, heat to reflux, then add acetone, filter, wash with acetone and ethanol in turn, and dry to obtain a modified PET.

[0006] Step B, add dichloromethane, trifluoroacetic acid, and modified PET into a container, add fatty acid eutectic phase change material after stirring, let stand for degassing after stirring to prepare a spinning solution, and then spin through an electrospinning machine, the spinning voltage is 15-18kV, the flow rate of the spinning solution is 2-3mL / h, and winding is performed to obtain a phase change energy storage fiber.

[0007] Preferably, in step B, the mass of the fatty acid eutectic phase change material is 60-100% of the mass of the modified PET.

[0008] Preferably, the preparation method of the fatty acid eutectic phase change material is: add fatty acid to a reaction vessel, keep warm at 80-90°C for 2-3h, then place in an ultrasonic instrument, ultrasonicate at 60-70°C for 2-3min, and cool to obtain a fatty acid eutectic phase change material. The fatty acid is any one or a combination of myristic acid, stearic acid, capric acid, and lauric acid.

[0009] Preferably, the preparation method of the grafted monomer is:

[0010] (1) Add ethanol, 2-methylallylamine and benzaldehyde DOPO intermediate in a molar ratio of (1-1.1):1 to a reaction vessel, heat to 60-70°C, stir and react for 5-8 hours, cool in an ice water bath, precipitate, filter and dry to obtain methylallyl DOPO intermediate. The reaction formula is as follows:

[0011]

[0012] (2) Add toluene and dichloromethane in a volume ratio of 1:(0.7-1), and methylallyl DOPO intermediate, fatty acid chloride and triethylamine in a molar ratio of 1:(1-1.3):(1-1.3) to the reaction vessel, react at room temperature for 6-10 hours, rotary evaporate, wash with petroleum ether, and recrystallize the product with dichloromethane to obtain a grafted monomer. The reaction formula is:

[0013]

[0014] Preferably, a phase change energy storage fabric is made of phase change energy storage fibers.

[0015] (III) Beneficial technical effects: The present invention uses grafting monomers to perform ultraviolet irradiation grafting modification on polyethylene terephthalate (PET), introduces aliphatic alkyl long chains and DOPO phosphorus-containing flame retardant structures into the PET matrix, and then electrospins with fatty acid eutectic phase change materials composed of capric acid, lauric acid, etc. The obtained phase change energy storage fibers exhibit different melting temperatures and melting enthalpy values, and have good phase change heat storage performance. It has broad application prospects in phase change heat storage fiber fabrics and the like.

[0016] The PET of the present invention is grafted with a DOPO phosphorus-containing flame-retardant structure, which significantly improves the flame-retardant properties of the PET fiber and exhibits a higher limiting oxygen index. At the same time, the PET is grafted with an aliphatic alkyl long chain, and has good compatibility with a fatty acid eutectic phase change material composed of capric acid, lauric acid, etc., and the grafted aliphatic alkyl long chain forms an association with the alkyl long chain of the fatty acid in the eutectic phase change material and physical crosslinking of the molecular chain, further improving the interface bonding force between the eutectic phase change material and the PET fiber, thereby reducing the adverse effects of the eutectic phase change material on the mechanical properties of the PET fiber, so that the PET fiber felt maintains a relatively high tensile strength, elongation at break and mechanical properties. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] The preparation method of the benzaldehyde-based DOPO intermediate is as follows: add 0.5 mol of terephthalaldehyde to a reaction vessel, dropwise add a 1,4-dioxane (15 mL) solution containing 0.55 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, react at 30°C for 7 hours, cool and filter, and recrystallize the product with ethanol to obtain the benzaldehyde-based DOPO intermediate. The structural formula is:

[0019] Example 1

[0020] (1) Add 500 mL of ethanol, 60 mmol of 2-methylallylamine, and 60 mmol of benzaldehyde-DOPO intermediate into a reaction vessel, heat to 70° C., stir and react for 5 h, cool in an ice-water bath, precipitate, filter, and dry to obtain methylallyl-DOPO intermediate.

[0021] (2) Add 200 mL of toluene and 200 mL of dichloromethane, 50 mmol of methyl allyl DOPO intermediate, 65 mmol of stearyl chloride and 65 mmol of triethylamine into a reaction container, react at room temperature for 6 h, rotary evaporate, wash with petroleum ether, and recrystallize the product with dichloromethane to obtain a grafted monomer.

[0022] (3) Add 10 g of stearic acid, 10 g of capric acid, and 80 g of lauric acid into a reaction container, keep warm at 90° C. for 2 h, then place in an ultrasonic instrument, ultrasonically treat at 70° C. for 2 min, and cool to obtain a fatty acid eutectic phase change material.

[0023] (4) Add a 0.3 g / L benzophenone acetone solution into the reaction vessel, stir and add a polyethylene terephthalate film, take out the film, dry and remove the acetone, then add the film into a 30 g / L grafting monomer ethanol solution, irradiate under a 800 W UV lamp in a nitrogen atmosphere, and perform the grafting reaction for 30 min. Take out the film, add it into toluene, heat and reflux for 6 h, then add acetone, filter, wash with acetone and ethanol in turn, and dry to obtain a modified PET.

[0024] (5) Add 450 mL of dichloromethane, 220 mL of trifluoroacetic acid, and 100 g of modified PET into a container, stir, and then add 60 g of fatty acid eutectic phase change material. Stir and let stand for degassing to prepare a spinning solution, which is then spun through an electrospinning machine at a spinning voltage of 18 kV and a spinning solution flow rate of 2 mL / h. Wind the solution to obtain a phase change energy storage fiber.

[0025] Example 2

[0026] (1) Add 600 mL of ethanol, 66 mmol of 2-methylallylamine, and 60 mmol of benzaldehyde-DOPO intermediate into a reaction vessel, heat to 60° C., stir and react for 8 h, cool in an ice-water bath, precipitate, filter, and dry to obtain methylallyl-DOPO intermediate.

[0027] (2) Add 200 mL of toluene and 140 mL of dichloromethane, 50 mmol of methylallyl DOPO intermediate, 50 mmol of myristoyl chloride and 50 mmol of triethylamine into a reaction vessel, react at room temperature for 10 h, rotary evaporate, wash with petroleum ether, and recrystallize the product with dichloromethane to obtain a grafted monomer.

[0028] (3) Add 10 g of myristic acid, 10 g of capric acid, and 80 g of lauric acid into a reaction container, keep warm at 80° C. for 3 h, then place in an ultrasonicator, ultrasonicate at 60° C. for 3 min, and cool to obtain a fatty acid eutectic phase change material.

[0029] (4) Add a 0.5 g / L benzophenone in acetone solution to the reaction vessel, stir and add a polyethylene terephthalate film, take out the film, dry and remove the acetone, then add the film to a 65 g / L grafting monomer in ethanol solution, irradiate under an 800 W UV lamp in a nitrogen atmosphere, and perform a grafting reaction for 60 min. Take out the film, add it to toluene, heat and reflux for 6 h, then add acetone, filter, wash with acetone and ethanol in turn, and dry to obtain a modified PET.

[0030] (5) Add 450 mL of dichloromethane, 220 mL of trifluoroacetic acid, and 100 g of modified PET into a container, stir, and then add 70 g of fatty acid eutectic phase change material. Stir and let stand for degassing to prepare a spinning solution, which is then spun through an electrospinning machine at a spinning voltage of 15 kV and a spinning solution flow rate of 2 mL / h. Wind and obtain a phase change energy storage fiber.

[0031] Example 3

[0032] (1) Prepare the grafted monomer according to the method of Example 1.

[0033] (2) Prepare fatty acid eutectic phase change material according to the method of Example 1.

[0034] (3) Add a 0.7 g / L benzophenone acetone solution into the reaction vessel, stir and add a polyethylene terephthalate film, take out the film, dry and remove the acetone, then add the film into a 100 g / L grafting monomer ethanol solution, irradiate under a 800 W UV lamp in a nitrogen atmosphere, and perform the grafting reaction for 90 min. Take out the film, add it into toluene, heat and reflux for 6 h, then add acetone, filter, wash with acetone and ethanol in turn, and dry to obtain a modified PET.

[0035] (4) Add 460 mL of dichloromethane, 230 mL of trifluoroacetic acid, and 100 g of modified PET into a container, stir, and then add 85 g of fatty acid eutectic phase change material. Stir and let stand for degassing to prepare a spinning solution, which is then spun through an electrospinning machine at a spinning voltage of 18 kV and a spinning solution flow rate of 3 mL / h. Wind the solution to obtain a phase change energy storage fiber.

[0036] Example 4

[0037] (1) Prepare the grafted monomer according to the method of Example 1.

[0038] (2) Prepare fatty acid eutectic phase change material according to the method of Example 1.

[0039] (3) Add a 1 g / L benzophenone acetone solution into the reaction vessel, stir and add a polyethylene terephthalate film, take out the film, dry and remove the acetone, then add the film into a 150 g / L grafting monomer ethanol solution, irradiate under a 800 W UV lamp in a nitrogen atmosphere, and perform the grafting reaction for 90 min. Take out the film, add it into toluene, heat and reflux for 6 h, then add acetone, filter, wash with acetone and ethanol in turn, and dry to obtain a modified PET.

[0040] (4) Add 460 mL of dichloromethane, 230 mL of trifluoroacetic acid, and 100 g of modified PET into a container, stir, then add 100 g of fatty acid eutectic phase change material, stir, let stand and degas to prepare a spinning solution, then spin through an electrospinning machine, the spinning voltage is 15 kV, the flow rate of the spinning solution is 3 mL / h, and wind to obtain a phase change energy storage fiber.

[0041] Comparative Example 1

[0042] (1) Prepare fatty acid eutectic phase change material according to the method of Example 1.

[0043] (2) Add 450 mL of dichloromethane, 220 mL of trifluoroacetic acid, and 100 g of polyethylene terephthalate into a container, stir, and then add 60 g of fatty acid eutectic phase change material. Stir and let stand for degassing to prepare a spinning solution, which is then spun using an electrospinning machine at a spinning voltage of 18 kV and a spinning solution flow rate of 2 mL / h. Wind the solution to obtain a phase change energy storage fiber.

[0044] Comparative Example 2

[0045] (1) Prepare methylallyl DOPO intermediate according to the method of Example 1.

[0046] (2) Add a 0.3 g / L benzophenone in acetone solution to a reaction vessel, stir and add a polyethylene terephthalate film, take out the film, dry and remove the acetone, then add the film to a 30 g / L methyl allyl DOPO intermediate in ethanol solution, irradiate under an 800 W UV lamp in a nitrogen atmosphere for grafting reaction for 30 min, take out the film, add it to toluene, heat and reflux for 6 h, then add acetone, filter, wash with acetone and ethanol in turn, and dry to obtain modified PET.

[0047] (3) Prepare fatty acid eutectic phase change material according to the method of Example 1.

[0048] (4) Add 450 mL of dichloromethane, 220 mL of trifluoroacetic acid, and 100 g of modified PET into a container, stir, and then add 60 g of fatty acid eutectic phase change material. Stir and let stand for degassing to prepare a spinning solution, which is then spun through an electrospinning machine at a spinning voltage of 18 kV and a spinning solution flow rate of 2 mL / h. Wind and obtain a phase change energy storage fiber.

[0049] The spinning solutions prepared in the examples and comparative examples were passed through an electrospinning machine to spin fiber felts, and then 10 cm×1 cm samples were made, and the tensile properties were tested using an electronic universal testing machine. The clamping distance was 50 mm, the tensile rate was 5 mm / min, and the initial tension was 0.1 cN.

[0050] The limiting oxygen index of fiber felt is tested according to GB / T 5454-1997. The larger the limiting oxygen index, the better the flame retardant performance.

[0051] The phase change heat storage performance of phase change energy storage fiber was tested by differential scanning calorimetry.

[0052] Table 1

[0053]

[0054]

[0055] As shown in Table 1, fatty acid eutectic phase change material is added to the PET fibers of each embodiment and comparative example, and the fibers show different melting temperatures and melting enthalpy values ​​and have good phase change heat storage performance. However, the tensile strength, elongation at break, and limiting oxygen index of the PET fiber felts of Examples 1-4 are significantly higher than those of Comparative Example 1. This is because polyethylene terephthalate (PET) is modified by ultraviolet irradiation grafting of grafted monomers, and aliphatic alkyl long chains are grafted into the PET matrix, which has good compatibility with the fatty acid low eutectic phase change material composed of capric acid, lauric acid, etc. At the same time, the aliphatic alkyl long chains grafted by PET form association and physical crosslinking of molecular chains with the alkyl long chains of fatty acids in the low eutectic phase change material, which further improves the interfacial bonding force between the low eutectic phase change material and the PET fiber, thereby reducing the adverse effects of the low eutectic phase change material on the mechanical properties of the PET fiber, so that the PET fiber felt exhibits higher tensile strength and elongation at break, and after ultraviolet irradiation grafting of the grafted monomers, a large amount of DOPO phosphorus-containing flame retardant structure is introduced into the PET matrix, which significantly improves the limiting oxygen index of the fiber and has better flame retardant properties.

[0056] Comparative Example 2 Using methyl allyl DOPO intermediate PET is grafted and modified, and a large amount of DOPO phosphorus-containing flame retardant structures are introduced into the PET matrix, which significantly improves the limiting oxygen index of the fiber and has better flame retardant properties. However, PET does not contain aliphatic alkyl long chains, and its compatibility and interfacial bonding force with fatty acid eutectic phase change materials are low, resulting in a large decrease in the tensile strength and elongation at break of PET fiber felt after adding phase change materials, and the mechanical properties become very poor.

[0057] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a phase change energy storage fiber, characterized in that: The preparation method is: Step A, adding an acetone solution containing benzophenone to a reaction container, adding a polyethylene terephthalate film after stirring, taking out the film, drying it, then adding the film to an ethanol solution containing a grafting monomer, irradiating it under an ultraviolet lamp in a nitrogen atmosphere, and performing a grafting reaction for 30-90 minutes, taking out the film, adding it to toluene, heating it to reflux, then adding acetone, filtering it, washing it, and drying it to obtain a modified PET; The structural formula of the grafted monomer is: n is any integer between 13 and 17; Step B, adding dichloromethane, trifluoroacetic acid, and modified PET into a container, adding fatty acid eutectic phase change material after stirring, standing and degassing after stirring to prepare a spinning solution, and then spinning and winding through an electrostatic spinning machine to obtain a phase change energy storage fiber.

2. The method for preparing the phase change energy storage fiber according to claim 1, characterized in that: In the step A, the mass concentration of benzophenone in the acetone solution is 0.3-1 g / L; the mass concentration of the grafting monomer in the ethanol solution is 30-150 g / L.

3. The method for preparing the phase change energy storage fiber according to claim 1, characterized in that: In the step B, the mass of the fatty acid eutectic phase change material is 60-100% of the mass of the modified PET.

4. The method for preparing the phase change energy storage fiber according to claim 3, characterized in that: The preparation method of the fatty acid eutectic phase change material is as follows: add fatty acid into a reaction container, keep warm at 80-90° C. for 2-3 hours, then place in an ultrasonic instrument, perform ultrasonic treatment at 60-70° C. for 2-3 minutes, and cool to obtain the fatty acid eutectic phase change material.

5. The method for preparing the phase change energy storage fiber according to claim 4, characterized in that: The fatty acid is any one or a combination of myristic acid, stearic acid, capric acid and lauric acid.

6. The method for preparing the phase change energy storage fiber according to claim 1, characterized in that: The voltage during spinning in step B is 15-18 kV, and the flow rate of the spinning solution is 2-3 mL / h.

7. The method for preparing the phase change energy storage fiber according to claim 1, characterized in that: The preparation method of the grafted monomer is: (1) Add ethanol, 2-methylallylamine and benzaldehyde DOPO intermediate in a molar ratio of (1-1.1):1 to a reaction vessel, heat to 60-70° C., stir and react for 5-8 hours, cool in an ice water bath, precipitate, filter and dry to obtain a methylallyl DOPO intermediate; The structural formula of the benzaldehyde-based DOPO intermediate is (2) Add toluene and dichloromethane in a volume ratio of 1:(0.7-1), and methylallyl DOPO intermediate, fatty acid chloride and triethylamine in a molar ratio of 1:(1-1.3):(1-1.3) into a reaction container, react at room temperature for 6-10 hours, rotary evaporate, wash, and recrystallize to obtain a grafted monomer.

8. The method for preparing the phase change energy storage fiber according to claim 7, characterized in that: The structural formula of the fatty acid chloride is n is any integer between 13 and 17.

9. A fabric made of phase change energy storage fiber obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Super fine composite terylene fibers storing energy through phase change, and preparation method

    CN100447315C

  • Resin composition and articles made therefrom

    CN109265996A

  • Environment-friendly polyester filament and manufacturing method thereof

    CN110438580A

  • Flame-retardant polyester fiber and preparation method thereof

    CN117306014A

Cited By

  • TPU material with high dimensional stability and preparation method thereof

    CN120289981A